Effect of microwave assisted alkali pretreatment and other pretreatment methods on some properties of bamboo fibre reinforced cement composites (2020)
This study investigated the effectiveness of microwave irradiation pre- treatment in combination with sodium hydroxide and other pretreatment methods on bamboo fiber cement composite characteristics. The materials used for this study include bamboo fibers, Portland cement, fine sand and calcium chloride. Microwave assisted sodium hydroxide (MT), sodium hydroxide alone (AA) and hot water (HT) treatments were used to pre-treat the bamboo fiber before its use in the cementitious composite. Mechanical tests were conducted after 7, 14 and 28 days while Fourier transformed Infrared spectroscopy (FTIR) with Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were used to characterize the composites. The use of microwave assisted alkali treatment is observed to have the best performance due to its more efficient role in improving fiber roughness, ductility and toughness in the cementitious composites.